PLD.08 Influence of the duration of the second stage on the likelihood of obstetric anal sphincter injury: a retrospective cohort study. (9th June 2014) - Aiken, CE; Prentice, A
Abstract : Objectives: To determine if duration of the second stage influences the likelihood of sustaining obstetric anal sphincter injuries (OASIS) in women undergoing spontaneous vaginal delivery. Methods: A retrospective cohort study was conducted over a 5-year period (2007–2012) in a single UK obstetrics centre including high-risk delivery unit and low-risk birthing centre. A cohort of 3839 nulliparous women with vertex-presenting, single, live-born infants at term who underwent spontaneous vaginal delivery was identified. Data were analysed using binomial logistic regression. Results: 247 out of 3839 (6.4%) women sustained OASIS. Independent risk factors for OASIS were birth-weight (OR 1.11; CI 1.075–154), maternal age (OR 1.04; CI 1.01–1.07), shoulder dystocia (OR 2.34; CI 0.83–5.67) and south-east Asian ethnicity (OR 2.73; CI 1.57–4.55). OASIS was less likely in those women who had epidural analgesia (OR 1.79; CI 1.22–2.69). The incidence of OASIS was not significantly different across second stages of different duration. Women who sustained OASIS had higher estimated blood loss, but there was no increase in the time to spontaneous neonatal respiration. Conclusions: Duration of the second stage of labour was not an independent risk factor for OASIS in spontaneously delivering nulliparous women. In other populations, the relationship between second stage length and OASIS may be confounded by instrumental deliveries. Accurate determination of OASIS risk factors is vital if standard-setting for maternity units is to include OASIS rates.